Hegemoni Fiqh Terhadap Penulisan Kitab Hadith - M. Dede Rodliyana (JOURNAL OF QUR'AN AND HADITH STUDIES, 2012)
This paper discusses the arguement behind the hegemony of fiqh in hadith literature. It discusses the opposition between ahl al-hadith and ahl al-fiqh, and the practice of hadith fabrication caused by political, ethnical and ideological debate between Muslims at that time. The article uses historical approach to trace the geneology of this opposition, and hadith criticism to study the kutub al-hadith